Compaction Quality Inspection Method of Soil-Rock Filled Embankment Based on Continuous Compaction Control Technology - Zhuoling He; Junyun Zhang (Advances in Civil Engineering)
Affected by the site construction conditions, the measurement passes of the Taihang Expressway K8 + 105 ∼ K8 + 341 (K8 worksite) in the Taihang Expressway did not meet the requirements of data analysis, and the quantity of the control points was insufficient so that the linear correlation between the dynamic deformation modulus () and the vibratory compaction value (VCV) was not strong. Therefore, the target value of VCV cannot be used to diagnose the Ev d compaction quality of soil-rock filler. This paper analyzes the roller measurement VCV value and in situ measurements Ev d value separately. Results reveal the difference between the VCV mean measured in the last two passes and the standard deviation of the measured VCV mean in the last pass are used as the main basis for the actual compaction quality. In addition, the Ev d mean in the last rolling can be used as an auxiliary judgment basis for the quality control of the compaction.